The palliative effect of camel milk on hepatic CYP1A1 gene expression and DNA damage induced by fenpropathrin oral intoxication in male rats - Ehsan H. Abu Zeid (Ecotoxicology and Environmental Safety, 2021)
The present study investigated the alleviating role of camel milk (CM) in the mitigation of fenpropathrin (FNP) type II pyrethroid induced oxidative stress, alterations of hepatic (CYP1A1) mRNA expression pattern, and DNA damage using the alkaline comet assay (SCGE) in male rats. Sixty male Sprague-Dawley rats were separated into six groups (n = 10): 1st control (C), 2nd corn oil (CO), 3rd (CM): gavaged CM 2ml/rat, 4th (FNP): gavaged FNP 7.09 mg/kg body weight (BW), 5th (FNP pro/co-treated): gavaged CM firstly for 15 days, then CM + FNP by the same mentioned doses and route, 6th (FNP + CM co-treated): gavaged FNP firstly followed by CM by the same mentioned doses and route. Rats were orally gavaged three times per week, day after day for 60 days. FNP exposure significantly reduced serum glutathione (GSH) levels, but significantly increased serum levels of superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), protein carbonyl (PCO), and 8hydroxy2deoxyguanosine (8OH2dG). Additionally, FNP exposure significantly up-regulated the mRNA expression levels of hepatic CYP1A1 and increased the SCGE indices in whole blood, liver, and spleen tissues of exposed male rats. Administration of CM significantly regulated the FNP induced oxidative stress, reduced hepatic CYP1A1 mRNA expression levels and values of comet assay indices particularly in the (CM + FNP pro/co-treated) group compared to the (FNP + CM co-treated) group. In conclusion, our results indicate, for the first time, that FNP retains an in vivo genotoxic potential at a dose of (1/10 LD50) and up-regulated hepatic CYP1A1 mRNA expression in male rats. Additionally, CM supplements may improve the genotoxic outcomes, oxidative stress, and altered CYP1A1 mRNA expression induced by FNP particularly in the pro/concurrent-treatment compared to the concurrent treatment alone.